New product ‘Insani’ low in market by Agro Bank branch Dungun / Nor Syuhaida Mat Zaki - Mat Zaki, Nor Syuhaida (Faculty of Business and Management, 2013)
Agro Bank is one of the leading financial institutions in Malaysia. insani is one of the products for education available at Agro Bank to support students to further their studies in local or overseas institutions of higher learning. The main reason of this research is to examine why this product has a low demand after four months existing in the market. Based on the matter, this research has been conducted for the evaluating purpose to evaluate the performance of Insani in terms of marketing strategy. This organization should emphasize marketing strategy to ensure that the objectives are achieved and thus reflect Agro Bank as an established organization. The selected company for this study is Agro Bank Malaysia Berhad because it is one of the banks in Malaysia well-known in the agricultural sector. This study focuses the new product “Insani” which has existed in the market. For the purpose of conducting this study, descriptive research was used. All the data collected are taken from primary and secondary data. The primary data are collected by interviewing staffs at Agro Bank and as well as distributing questionnaires. Besides that, the secondary data are collected from the intranet (Agro Bank website), internet, manual of Insani and media printed (newspapers and magazines). Based on the findings analysis, it is able to identify the important factors influencing the demand of Insani. Hopefully, from the findings of this research, it can give advantages to the company and the demand of Insani.